The Integration of Artificial Intelligence into English Language Teaching: Voices from Vietnamese EFL Teachers - Thao Quoc Tran; Tu Minh Nguyen (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
The advent of sophisticated artificial intelligence (AI) technologies has resulted in the significant influence of AI on the process of English language teaching (ELT) and learning. Notwithstanding the greater penetration of AI into language education, little research focuses on English as a foreign language (EFL) teachers’ perspectives on AI integration into English classrooms at tertiary education in the Vietnamese context. This qualitative study examined four Vietnamese EFL teachers’ perceived benefits and challenges of utilizing AI in English language teaching. To analyse qualitative data from the semi-structured interviews, the thematic analysis approach was adopted. The findings revealed that Vietnamese EFL teachers perceived AI as an essential teaching aid in their teaching process as the adoption of AI could enhance their teaching methods. The current study has important practical implications for language teachers, learners, and policymakers such as the stimulation of personalized learning, increase in student motivation and engagement in learning activities, and difficulties in using AI in ELT to promote an improvement in English language education quality.